Progress and Pitfalls of Bacteriophage Therapy in Critical Care: A Concise Definitive Review. (8th March 2021) - Valente, Luca; Prazak, Josef; Que, Yok-Ai; Cameron, David R.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objective: Bacterial infections caused by antibiotic-resistant pathogens are a major problem for patients requiring critical care. An approach to combat resistance is the use of bacterial viruses known as "phage therapy." This review provides a brief "clinicians guide" to phage biology and discusses recent applications in the context of common infections encountered in ICUs. Data Sources: Research articles were sourced from PubMed using search term combinations of "bacteriophages" or "phage therapy" with either "lung, " "pneumonia, " "bloodstream, " "abdominal, " "urinary tract, " or "burn wound." Study Selection: Preclinical trials using animal models, case studies detailing compassionate use of phage therapy in humans, and randomized controlled trials were included. Data Extraction: We systematically extracted: 1) the infection setting, 2) the causative bacterial pathogen and its antibiotic resistance profile, 3) the nature of the phage therapeutic and how it was administered, 4) outcomes of the therapy, and 5) adverse events. Data Synthesis: Phage therapy for the treatment of experimental infections in animal models and in cases of compassionate use in humans has been associated with largely positive outcomes. These findings, however, have failed to translate into positive patient outcomes in the limited number of randomized controlled trails that have been performed to date. Conclusions: Widespread clinical implementation of phage therapy depends on success in randomized controlled trials. Additional translational and reverse translational studies aimed at overcoming phage resistance, exploiting phage-antibiotic synergies, and optimizing phage administration will likely improve the design and outcome of future trials.